2021
DOI: 10.1016/j.bioflm.2021.100055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-peroxide generating electrochemical bandage is active in vitro against mono- and dual-species biofilms

Abstract: Biofilms formed by antibiotic-resistant bacteria in wound beds present unique challenges in terms of treating chronic wound infections; biofilms formed by one or more than one bacterial species are often involved. In this work, the in vitro anti-biofilm activity of a novel electrochemical bandage (e-bandage) composed of carbon fabric and controlled by a wearable potentiostat, designed to continuously deliver low amounts of hydrogen peroxide (H 2 O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In previous work, we showed that this e‐bandage markedly reduced in vitro bacterial biofilms within 48 h of treatment. [ 30 ] Here, we assessed this H 2 O 2 producing e‐bandage in a mouse wound infection model.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we showed that this e‐bandage markedly reduced in vitro bacterial biofilms within 48 h of treatment. [ 30 ] Here, we assessed this H 2 O 2 producing e‐bandage in a mouse wound infection model.…”
Section: Discussionmentioning
confidence: 99%
“…With the e‐bandage, an agar membrane biofilm model was used to simulate physical properties of the wound bed and validate the technology prior to animal testing. Polarized e‐bandages were active against mono‐ and dual‐species bacterial and yeast biofilms (Raval et al, 2022 ; Raval, Mohamed, et al, 2021 ). In this work, validation was extended to assessment of e‐bandages against ex vivo biofilms grown on porcine explants.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of a hydrogel for the liquid medium was used to transform e‐scaffolds into electrochemical bandages (e‐bandages) for direct application to wound surfaces. The e‐bandage reduced in vitro biofilms of mono‐ and dual‐species micro‐organisms, including methicillin‐resistant S. aureus , multidrug‐resistant A. baumannii and yeast (Mohamed et al, 2021 ; Raval et al, 2022 ; Raval, Mohamed, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm Eradication Assay. 35,36 Biofilm eradication experiments were performed using a pegged-lid microtiter plate assay to determine the MBEC values for compounds of interest, as previously described. 1,2 Briefly, 125 mL of midlog phase culture diluted to ca.…”
Section: ■ Conclusionmentioning
confidence: 99%